2022
DOI: 10.3390/cells11172660
|View full text |Cite
|
Sign up to set email alerts
|

A Combination Therapy of Urolithin A+EGCG Has Stronger Protective Effects than Single Drug Urolithin A in a Humanized Amyloid Beta Knockin Mice for Late-Onset Alzheimer’s Disease

Abstract: In the current study, for the first time, we study mitophagy enhancer urolithin A and a combination of urolithin A+green tea extract EGCG against human Aβ peptide-induced mitochondrial and synaptic, dendritic, inflammatory toxicities and behavioral changes in humanized homozygous amyloid beta knockin (hAbKI) mice of late-onset Alzheimer’s disease (AD). Our findings reveal significantly increased positive effects of urolithin A and a combination treatment of urolithin A+EGCG in hAbKI mice for phenotypic behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…UA increased muscle strength and physical performance in a 6 min walk test in elderly humans after four months of supplementation [80]. Other studies reported that UA improved motor activity in the rotarod test and increased total distance traveled and average speed in the open field test in young C57BL/6J mice [81] and in 3xTg AD mice [82]. However, we noted that UA decreased the distance travelled by 3xTgAD mice in the open field test (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…UA increased muscle strength and physical performance in a 6 min walk test in elderly humans after four months of supplementation [80]. Other studies reported that UA improved motor activity in the rotarod test and increased total distance traveled and average speed in the open field test in young C57BL/6J mice [81] and in 3xTg AD mice [82]. However, we noted that UA decreased the distance travelled by 3xTgAD mice in the open field test (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Ellagic acid regulated intestinal microbiota through increasing Lactobacillus species and decreasing Escherichia coli levels [ 103 ], enhanced the immune response by modulating different signalling pathways and increasing the intestinal mucosal barrier function via activating Zonula occludens-1 and Occludin proteins, which are implicated in the tight junction structure of enterocytes and intestinal permeability [ 104 ]. Following polyphenol treatment, mitochondrial dysfunction and the levels of some neuroinflammatory biomarkers were reduced in mouse brains, and dendritic spines and lengths were significantly increased [ 105 ]. Moreover, in the hippocampus, the Nrf2/HO-1 pathway was activated, and the levels of IL-1β, IL-6 and TNF-α were reduced [ 106 ].…”
Section: Biphasic Action Of Dietary Polyphenols and Intestinal Flora ...mentioning
confidence: 99%
“…Since the early 21 st century, we have also been able to measure the bioenergetics of mitochondria in cells treated with pharmacological drugs by using a Seahorse XFe96 Flux Analyzer (Gu et al., 2021; Kshirsagar, Sawant, Morton, Reddy, & Reddy, 2021a; Luz, Smith, Rooney, & Meyer, 2015). In our lab, we have used the following pharmacological drugs as mitophagy enhancers: urolithinA, actionin, tomatidine, and nicotinamide riboside (Kshirsagar et al., 2022; Kshirsagar, Sawant, Morton, Reddy, & Reddy, 2021b). There are three main limitations to measuring mitochondrial respiration using the Seahorse bioanalyzer: the cost is high, a single assay can only use four injectable compounds, and drug injection may lead to inaccurate/misleading data by interfering with sensor fluorescence or the plastic plate (Horan, Pichaud, & Ballard, 2012).…”
Section: Commentarymentioning
confidence: 99%